Communicating Autism on the Internet The Emerging of Neurodiversity Movement in Indonesia - Hersinta (Curtin University, 2020)
This doctoral thesis aims to provide a study of Autism and advocacy movement on the internet from Indonesian cultural context by applying a critical disability studies approach. The thesis concludes that Autism culture on the internet, in the form of the neurodiversity movement, provide a form of self-awareness among some Autistics in this study – to view themselves beyond the medical definition of Autism that perceives them as ‘disabled’ by a mainstream or neurotypical culture.